Surveillance of SARS-CoV-2 in extensive monitoring of municipal wastewater: key issues to yield reliable results - F. Cutrupi; M. Cadonna; S. Manara; P. Foladori (Water Science and Technology, 2021)
Several studies have detected SARS-CoV-2 in the stool of infected people as in urban wastewater. The quantification of SARS-CoV-2 in wastewater appears today as a powerful tool that can help in wastewater-based epidemiology (WBE). The goal is to improve the prediction of new waves of COVID-19 outbreaks and provide an early warning of the evolution of the infection. In this research, we highlighted some practical and scientific aspects that emerged during an extensive ongoing monitoring campaign carried out on a large number of wastewater treatment plants located in the province of Trento (North Italy) and aimed at the detection of SARS-CoV-2 in raw municipal wastewater. The open issues underline are related to the collection and storage (sampling protocol, storage and heat treatment), to the molecular analysis (enrichment phase), and to the mathematical calculation of SARS-CoV-2 load in wastewater, suitable for WBE (standard curve to obtain the concentration of genomic units and flow rate measurements). This study provides some insights that can help in the implementation of surveillance plans in other regions. HIGHLIGHTS It is possible to quantify SARS-COV-2 from wastewater.; Wastewater based epidemiology is a useful tool for predicting new outbreaks.; Heat treatments make the virus more easily detectable.; Several storage protocols have been tested.;